CROPS’ PRODUCTIVITY IN SHORT-TERM ROTATIONS DEPENDING ON TILLAGE AND FERTILIZATION IN THE FOREST-STEPPE OF UKRAINE - Pospelov, S. V.; Levchenko, L. M.; Chaika, T. O.; Perepelytsia, A. A.; Shandyba, V. O.; Popova, K. M. (Scientific Progress & Innovations, 2020)
For the first time, the influence of tillage methods on sugar beet productivity, the yield of winter wheat, barley and sainfoin depending on fertilization background in short-term rotations has been found out for the conditions of the Left-Bank Forest-Steppe of Ukraine, during a long stationary experiment on typical weaklyalkalinized black soil,. The problem of basic tillage methods effect on water and soil agrochemical indicators has been further developed. Subsurface tillage, plowing, combined tillage at the background of applying organic and mineral fertilization syste have been established scientifically. The peculiarities of phytocenoses formation of sugar beet, winter wheat and barley, the spreading of diseases in them depending on tillage and fertilization rates have been revealed. A significant role in increasing the productivity of sugar beets, winter wheat, barley and other crops in rotation belongs to effective tillage and fertilization, which affect the provision of plants with moisture and nutrients during their growing season as well as the formation of phytosanitary condition of crops. These problems were studied in research papers of V. F. Zubenko, M. K. Shykula, О. H. Tarariko, A. D. Balaiev, А. М. Maliienko, S. P. Tanchyk, Yu. P. Manko, V. M. Yakymenko, L. A. Barshtein, І. S. Shkarednyi, I. D. Prymak, Ya. P. Tsvei and others. Currently, different systems of tillage and fertilization of sugar beet and other crops of grain-beet rotation are used for different areas of beet sowing in Ukraine. These systems are changed and improved taking into account effective tillage and proper distribution of fertilizers between crops in rotation fields as well as natural and climatic conditions of a particular area. At the same time, in short-term rotations, the tillage system depending on fertilization system both for sugar beet, winter wheat and barley hasn’t sufficiently been developed and studied. The problem of subsoil tillage, plowing, and combined tillage in accordance with crop rotation in short-term successions hasn’t been solved yet. Our research was focused on solving this current problem. Field studies were conducted as part of the stationary experiment at Veselyi Podil Research and Breeding Station of the Institute of Bioenergy Crops and Sugar Beet of the National Academy of Agrarian Sciences of Ukraine from 2013 to 2016 in short-term grain-beet rotations with different methods of basic tillage for sugar beet, winter wheat and sainfoin depending on fertilization backgrounds. Field stationary experiment was the main method of research, supplemented by analyses according to the generally accepted techniques in agro-chemistry, crop growing and soil management. The station is located in Semenivka district of Poltava region in the southeastern part of the Left-Bank Forest-Steppe of Ukraine. In short-term rotation, plowing to a depth of 30–32 cm under sugar beet and subsoil loosening to 20–22 cm under cereals at the background of further applying N140P90K90 + straw under beet ensured the highest productivity of sugar beet: the yield of beetroots and sugar were 39.9 t/ha and 6.83 t/ha, respectively.